2019
DOI: 10.3390/md17080455
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Bases from Sea Cucumber Alleviate Obesity by Modulating Gut Microbiota

Abstract: This study evaluated the effects of long-chain bases from sea cucumber (SC-LCBs) on modulation of the gut microbiota and inhibition of obesity in high fat diet-fed mice. Results showed that SC-LCBs exerted significant antiobese effects, which were associated with the inhibition of hyperglycemia and lipid accumulation. SC-LCBs also regulated serum adipocytokines toward to normal levels. SC-LCBs caused significant decreases in Firmicutes, Actinobacteria phylum, and obesity-related bacteria (Desulfovibro, Bifidob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“… 36 Ruminococcus 1 is a highly heterogeneous genus in which some species have probiotic effects, 36 whereas others are considered pathogenic. A prior study found a positive correlation between the abundance of Romboutsia and obesity, 37 suggesting that these bacteria play a negative role in lipid metabolism. Interestingly, Faecalibaculum , a genus believed to promote the beneficial generation of SCFAs in the intestines, 38 had an increased relative abundance in NAFL/NASH mice, as did Bifidobacterium , a genus that has long been considered a probiotic.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Ruminococcus 1 is a highly heterogeneous genus in which some species have probiotic effects, 36 whereas others are considered pathogenic. A prior study found a positive correlation between the abundance of Romboutsia and obesity, 37 suggesting that these bacteria play a negative role in lipid metabolism. Interestingly, Faecalibaculum , a genus believed to promote the beneficial generation of SCFAs in the intestines, 38 had an increased relative abundance in NAFL/NASH mice, as did Bifidobacterium , a genus that has long been considered a probiotic.…”
Section: Discussionmentioning
confidence: 99%
“… Zeng et al (2019) performed a clinical study and found that Blautia , Romboutsia , Ruminococcus , and Dorea were positively correlated with indicators of bodyweight and serum lipids. In addition, Hu et al (2019) showed that both Romboutsia and Desulfovibrio were obesity-related bacteria. Li et al (2018) reported a significant relationship between Romboutsia and serum TC, TG, and LDL-C levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among these is Ruminiclostridium_ 9, a bacterial group which has been previously connected to obesity and other metabolic disorders ( Wang et al, 2019 ), although these results are regarded with caution. While some studies have proposed that obese mice have a higher abundance of Ruminiclostridium_9 in their fecal microbiota than the leaner counterparts ( Hou et al, 2019 ; Luo et al, 2019 ; Wang et al, 2020 ), others have shown that Ruminiclostridium_9 is instead negatively correlated with obesity ( Zhao et al, 2017 ; Zhu et al, 2018 ; Hu et al, 2019 ). Another example of a MSTN-edited upregulated group in the cecum is Succinivibrio , a bacteria that has high potential for fiber degradation ( Hippe et al, 1999 ) and thus can improve metabolism.…”
Section: Discussionmentioning
confidence: 99%